Scholarly article seeking chances the good and bad / Siti Mariana Hamzah and Nur Atiqah Azmi - Hamzah, Siti Mariana; Azmi, Nur Atiqah (2015)
Scholarly article or also known as pre-reviewed journal articles are the writing that produced by a professional writer or someone who belong to this field of work. Scholarly articles are commonly related to students, researcher, professionals and anyone that going to work on writing. Before the ages of internet exploded, it is quite difficult to students or researcher to look for the scholarly articles. This is because the articles are in printed form. So they must go to the library or information center to get the journal. However, the articles seeking has been changes because of internet. They can get the articles easily from the electronic journals or access from the library. The sources from the internet sometimes were not trusted. This can be harder to deal with. There are some scholarly articles or journals that being publish in web version but we don t know whether the journal going through the scholarly process or not. Like wise to the articles that we find from one of the databases from the library. Fortunately most journals in on-line version and reliable. How about the reference like Wikipedia? The wiki is actually one of the community edited document. It means everyone can add or change the information. It still can use as one of the inspire idea but not for scholarly sources. The reviewers might be someone who not particular in the area.